PENGARUH CREDIBILITY DAN ATTRACTIVENESS CELEBRITY ENDORSER TERHADAP PURCHASE DECISION PADA SITUS BELANJA ONLINE SHOPEE DI INDONESIA - Putri Kumala Dewi; Islahuddin Daud; Aslamia Rosa (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
This study aims to determine the effect of the credibility and attractiveness of Prilly Latuconsina as a celebrity endorser on the purchase decision at online shopping sites “Shopee” in Indonesia both partially and simultaneously. This study uses primary data obtained from the questionnaire. The number of samples was 100 respondents and using the convenience sampling method. The analysis techniques that be used are multiple linear regression analysis, F test, and t test. The results showed that the credibility and attractiveness of the celebrity endorser had a simultaneous effect on the purchase decision at online shopping site “Shopee”. The partial test results show that the credibility of celebrity endorser has a positive and significant effect on the purchase decision, while the attractiveness of celebrity endorser does not effect the purchase decision at online shopping sites “Shopee”. Through the adjusted coefficient of determination test (Adjusted R Square), a value of 0.193 is obtained, it means that 19.3% of purchasing decision as the dependent variable can be explained by credibility and attractiveness as independent variables. While the remaining 80.7% is explained by other variables which are not examined in this study.